FORAMINIFERI PLANCTONICI ED OSCILLAZIONI CLIMATICHE NELLA CAROTA BAN 84-27 (MEDITERRANEO ORIENTALE) - VIOLANTI, DONATA; SACCÀ, DOMENICA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Planktonic foraminifera from Core BAN 84-27, recovered from a Mediterranean Ridge site located north of the Katia Basin (Eastern Mediterranean) were quantitatively investigated. The sediments are Late Pleistocene to Holocene in age; the sequence of sapropels, from S-1 to S-9, is almost complete, except S-2 and S4, which are missing and provides the lithostratigraphic framework. One tephra layer (Y-5) was identified. Peaks of abundance of Neogloboquadrina eceri were recognized in sapropels S-6 and S-8; these findings, recorded also in the reference cores, support the peculiarity of S-6 and S-8, which were deposited during cold intervals.A climatic curve, based on the relative abundance of climatically significant planktonic foraminifera, was constructed; its warm and cold peaks are correlatable to the fluctuations recorded in other Eastern Mediterranean cores (Core EASTW 29, Cobblestone Area 3; Core EASTW 6 and 45, Cobblestone Area 4; Cores KS-09 and RC9-181). The maximum diameter of Orbulina universa increases in accordance with relative abundance of climatically warmer species. This simple parameter seems to be an useful tool for paleoclimatic interpretations of Quaternary sediments, with larger sizes correlatable to warm intervals. Peaks of abundance of Neogloboquadrina eggeri were recognized in sapropels S-6 and S-8; these findings, recorded also in the reference cores, support the peculiarity of S-6 and S-8, which were deposited during cold intervals. The distribution of planktonic gastropods (Thecosomata Euthecosomata and Heteropoda) was investigated and correlated with the foraminiferal curve. The paleoclimatic value of pteropods is also evident in Core BAN 84-27: well diversified assemblages, characterized by a great abundance of warm water species (Limacina inflata), were observed in sapropels S-1 and S-9 and in other warm episodes. Poor assemblages, with sparse specimens of cold water species (L. retroversa) are present in cold episodes and in sapropel S-8. Intervals correlative to isotopic stages 1 to ...